A STUDY OF SPEAKING COMMON UNIVERSITY LEARNER BARRIERS IN INDONESIAN CONTEXT - Sampelolo, Rigel; Tandikombong, Matius; Pongsapan, Nehru Pasoloran; Lura, Hans (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
Learning foreign languages for worldwide communication has become increasingly important for university students as the desire for global integration has grown. As a result, English as a second language should become a required course at the university level. However, achieving their speaking competency level in this situation is difficult for English learners. Due to specific limitations in English speaking barriers, this research was conducted to find out the learners' barriers to speaking English. This research applied a descriptive qualitative method in analyzing the data collected. The subjects of this research were the sixth-semester learners from five different study programs at the Christian University of Indonesia (UKI) Toraja (UKI Toraja). The researchers used a snowball sampling technique and elected 20 students as participants. To collect the data, the researchers used semi-structured interviews. The result of the data analysis showed that the sixth-semester learners found barriers in speaking English. Those barriers are: 1) psychological barriers (anxiety, shyness, nervousness, lack of confidence, fear of making mistakes), and 2) linguistic barriers (lack of vocabulary, lack of grammar